Does urbanization reduce the multi-functional value of cultivated land? Evidence from China - Shi, Wei; Liu, Dandan (Frontiers in Environmental Science, 2023)
The contradiction between urbanization and cultivated land conservation needs to be resolved urgently. The coupling of cultivated land production, compound utilization and ecological protection is a hot topic for policy makers and researchers. Based on the panel data of 31 provinces in China from 2002 to 2018, this paper estimated the impact of urbanization on the quantity and structure of cultivated land functional value using a fixed effect model. The results show that the multi-functional value of cultivated land fluctuates in time series. There was obvious synergistic relationship among different functions of cultivated land, and the synergistic relationship was gradually weakened. Urbanization did not decrease the multi-functional value of cultivated land, and the producing function of cultivated land was improved most obviously. The value of producing function and social security function in main-producing areas is the most obvious response to urbanization. The culture of main marketing areas has the highest response to urbanization, and urbanization has reduced the ecological function of grain main marketing areas. Urbanization has reduced the diversified types of cultivated land, and the function positioning of cultivated land is gradually obvious. Therefore, policy makers should pay attention to the dialectical relationship between the total amount and structure of multi-functional cultivated land and implement regional differentiation policy of multi-functional cultivated land utilization.